Implementation method experiments on student results on substances being material and its amendment in class VII SMP Negeri 22 - Eka Trisianawati; Nurhayati Nurhayati; Lusi Beniwati (Journal of Physics: Theories and Applications, 2017)
The aims of this research were to know: (1) the average student learning outcomes in states of matter and changes the material that is taught by an experimental method in class VII SMP Negeri 22 Pontianak; (2) the average student laerning outcomes in states of matter and changes the material that is taught by  conventional method in class VII SMP Negeri 22 Pontianak; (3) the average difference in student learning outcomes given the experimental method to the average student learning outcomes given conventional methods in states of matter and changes the material in class VII SMP Negeri 22 Pontianak . This research was a quasi-experimental design with Nonequivalent Control Group Design. The study population was all students of class VII SMP Negeri 22 Pontianak which consists of five classes, namely class VII A, VII B, VII C, VII D and E VII academic year 2015/2016, with a sampling technique that cluster random sampling. Based on the results of class VII A lottery was chosen as an experimental class and class VII D as the control class. The data collection technique used is the technique of measurement. Data collection tool used is a form of essay test. The hypothesis was tested using the t-test. Based on the results of data analysis can be concluded that: (1) the average student learning outcomes in states of matter and changes the material that is taught by an experimental method in class VII SMP Negeri 22 Pontianak is 64.96, (2) the average student learning outcomes in material states of matter and the changes that are taught by conventional methods in class VII SMP Negeri 22 Pontianak is 49.85, and (3) there are differences in the average student learning outcomes given the experimental method to the average student learning outcomes given in the conventional method material phase transition and changes in class VII SMP Negeri 22 Pontianak.